Kualitas Kinerja Pelayanan Publik Dukcapil Kota Binjai: Dampak Sasaran Program dan Kualitas SDM - Wahyu Firmansyah; Elida Elfi Barus (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to analyze the influence of program target accuracy and human resources (HR) quality on the quality of public service performance at the Department of Population and Civil Registration (Dukcapil) of Binjai City. Amidst the digital transformation through the E-Disdukcapil application, administrative challenges such as low participation in death certificate processing and limited personnel quantity have become central issues. This research employs a quantitative approach with a causal-associative design. The research population includes the entire community of Binjai City utilizing Adminduk services, with a sample of 100 respondents determined through accidental sampling techniques. Data were collected using structured questionnaires and analyzed via multiple linear regression using SPSS software. The results indicate that program target and HR quality variables simultaneously have a significant positive impact on the quality of public service performance. Partially, HR quality was found to have a more dominant contribution compared to program targets. The findings identify operational barriers in the form of limited staff numbers and low effectiveness in socializing door-to-door programs. The study concludes by suggesting the strengthening of personnel capacity through digital training and optimizing public communication strategies to support the sustainability of service innovation in Binjai City.